Particle Residence Time Distribution in a Concurrent Multiphase Flow Reactor: Experiments and Euler-Lagrange Simulations - Unger, Laura; Gomez Bonilla, Juan Sebastian; Dos Santos, Dyrney Araujo; Bück, Andreas (Processes, 2022)
The present work focuses on investigating the residence time behavior of microparticles in a concurrent downer reactor through experiments and numerical simulations. For the numerical simulations, a three-dimensional multiphase model was developed using the Euler-Lagrange approach. The experiments were performed in a 0.8 m-long steel reactor with gravitational particle injection. The effects of different operating conditions, e.g., the sheath gas velocity on the particle residence time distribution were assessed. An increase in the sheath gas flow rate led to a decrease in the peak residence time, although the maximum residence time increased. Regarding the lowest sheath gas flow rate, the particles' peak residence time was twice as high compared to the peak residence time within the highest flow rate. The particles' residence time curves presented a broad distribution coinciding with the size distribution of the powder. The numerical results agreed with the experimental data; thus, this study presents a numerical model for predicting the particle residence time behavior in a concurrent downer reactor. Furthermore, the numerical simulations contributed to a better understanding of the particle residence time behavior inside a concurrent downer reactor which is essential for optimizing thermal rounding processes. Dimensionless correlations for the observed effects are developed.
CRIS-Team WoS Importer:2022-06-17
Keywords: residence time distribution; axial flow structure; downer reactor; gas-particle flow; thermal rounding